2022
DOI: 10.1094/mpmi-05-21-0122-r
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and Transcriptomic Analyses of Dalbergoid Legume Peanut Reveal a Divergent Evolution Leading to Nod-Factor-Dependent Epidermal Crack-Entry and Terminal Bacteroid Differentiation

Abstract: Root nodule symbiosis (RNS) is the pillar behind sustainable agriculture and plays a pivotal role in the environmental nitrogen cycle. Most of the genetic, molecular, and cell-biological knowledge on RNS come from model legumes that exhibit a root-hair mode of bacterial infection in contrast to the Dalbergoid legumes exhibiting crack-entry of rhizobia. As a step towards understanding this important group of legumes, we have combined microscopic analysis and temporal transcriptome to obtain a dynamic view of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 100 publications
1
23
0
Order By: Relevance
“…Rhizobia were present in most of the cells where the auxin response was active. After endocytosis, the bacteroids continue to have a small, elongated shape (E‐type), which eventually are converted to a spherical shape (Sinharoy & DasGupta, 2009; Raul et al ., 2022). Interestingly, the nuclear auxin response was present only in those cells where the bacteroids are of E‐type (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizobia were present in most of the cells where the auxin response was active. After endocytosis, the bacteroids continue to have a small, elongated shape (E‐type), which eventually are converted to a spherical shape (Sinharoy & DasGupta, 2009; Raul et al ., 2022). Interestingly, the nuclear auxin response was present only in those cells where the bacteroids are of E‐type (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RNA sequencing (RNAseq) profiling of different stages of nodule development revealed that the transcriptomic signature in peanut is both conserved as well as diversified in different modules compared to model legumes (Raul et al ., 2022). In the present study, using promoter‐aided reporter analysis and RNA in situ hybridization (ISH), we show that spatial expression of NIN is restricted to the root pericycle and inner cortical layers during nodule primordia initiation.…”
Section: Introductionmentioning
confidence: 99%
“…In A. hypogeae , known symbiotic genes acting in the common IT mediated nodulation (125 peanut orthologs) are also expressed during symbiosis ( Figure 2 ). The majority of DEGs are observed during nodule functioning, then nodule organogenesis and finally infection ( Raul et al, 2022 ). Transcriptomic analyses of a time-course experiment in A. evenia allowed the identification of DEGs at early and late stages of the symbiotic interaction.…”
Section: Constitutive Intercellular Infection Processmentioning
confidence: 99%
“…Some immune response-activated genes, namely TIR-NBS-LRR, LRR-RLK, EF-hand pair protein, and WAKL (Kumar et al 2020), were also induced excessively in G9 plants compared with G3 plants. Despite the slight induction of defense response-related genes, namely FLS2, (Liu et al 2017), in G9 plants, as well as the marginally suppressed disease resistance proteins, namely RPM1 (NBS-LRR, LRR, and NB-ARC) and RPS2, in G3 plants, both defense-related gene induction (i.e., PR1) and the E. meliloti secretion system, which triggers the ETI process (i.e., HSP90), were induced to a larger extent in G3 plants, indicating an enhanced control of rhizobial proliferation and an elevated defense/resistance of G3 plants to bacteroids (Li et al 2020a, b;Raul et al 2021). The ubiquitin proteasome system (UPS) induces, regulates, and terminates plant responses to stress, and E3 ubiquitin ligase can positively regulate plant tolerance to biological stress (Li et al 2020a, b).…”
Section: Plant Immunity Plays Vital Roles In Determining the Specific...mentioning
confidence: 99%